2016
DOI: 10.1186/s12886-016-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the SRK/T formula using A-Scan ultrasound biometry after phacoemulsification in eyes with short and long axial lengths

Abstract: BackgroundThe SRK/T formula is one of the third generation IOL calculation formulas. The purpose of this study was to evaluate the performance of the SRK/T formula in predicting a target refraction ±1.0D in short and long eyes using ultrasound biometry after phacoemulsification.MethodsThe present study was a retrospective analysis, which included 38 eyes with an AL < 22.0 mm (short AL), and 62 eyes ≥24.6 mm (long AL) that underwent uncomplicated phacoemulsification. Preoperative AL was measured by ultrasound b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Thanks to the developing biometric devices and formulas, it has become possible to reach the targeted refractive results after phacoemulsification surgery (9). Today, one of the most important goals of cataract surgery is to achieve the desired refractive result (10)(11)(12). Kaya et al evaluated the SRK-T and SRK-2 biometric formulas in eyes with a short axial length in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the developing biometric devices and formulas, it has become possible to reach the targeted refractive results after phacoemulsification surgery (9). Today, one of the most important goals of cataract surgery is to achieve the desired refractive result (10)(11)(12). Kaya et al evaluated the SRK-T and SRK-2 biometric formulas in eyes with a short axial length in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The mean IOP before surgery was 14.9±1.8[10][11][12][13][14][15][16][17][18][19][20] mm Hg in the SRK-T group and 14.5±1.7[11][12][13][14][15][16][17][18] mm Hg in the SRK-2 group. The average IOP at 3 months after surgery was 13.5±1.67[10][11][12][13][14][15][16][17] mm in the SRK-T group and 13.8±1.86[11][12][13][14][15][16][17][18][19] mm Hg in the SRK-2 group. There was no difference between the two groups in terms of IOP values before and after surgery.…”
mentioning
confidence: 99%
“…Narvaez et al have reported equal refractive results when compared the effectiveness of Hoffer Q, Holladay 1, Holladay 2 and SRK/T formulas in short, medium and long eyes [17]. Karabela et al have obtained good outcomes in both short and long eyes by using SRK/T formula [18]. In contrast to these studies, Aristodemou et al have demonstrated the superiority of SRK/T and Hoffer Q in eyes with AL greater than 26 mm, and less than 21.5 mm respectively in their comprehensive study [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ultrasound technique requires physical direct or indirect (immersion technique) contact of transducer with the cornea. Both ultrasound (US) A-scan biometry and non-contact PCI based devices are used for calculating IOL power 6,8 . AL in ultrasound method is measured from corneal vertex to the internal limiting membrane (ILM) 9 .…”
Section: Introductionmentioning
confidence: 99%